2016
DOI: 10.4038/ouslj.v11i0.7347
|View full text |Cite
|
Sign up to set email alerts
|

Role of Silicon on Enhancing Disease Resistance in Tropical Fruits and Vegetables: A Review

Abstract: Silicon (Si) has proven to enhance disease resistance in a wide range of tropical fruits and vegetables. It has been used in controlling various diseases: mildews, rots, moulds, wilt, blight, anthracnose and leaf spots. However, the highest number of records was available on reducing diseases of powdery mildews on fruits and vegetables belonging to the family Cucurbitaceae. Siliconmediated defense responses in plant pathosystems are mainly attributed to the physical resistance, which involves reduced penetrabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 63 publications
0
7
0
Order By: Relevance
“…It also satisfies the requirements, such as, no toxicity to pathogens, plants or animals, not affecting plant growth, development and yield, broad spectrum of defense and long lasting (Kessman et al, 1994;Tally et al, 1999;Kuc, 2001). There were several studies in the past proved that the enhanced natural disease resistance could be achieved with silicon (Si) treatment, in a wide range of tropical and sub-tropical fruits and vegetables (Weerahewa and Somapala, 2016;Huang et al, 2011;French-Monar et al, 2010). This has been achieved through different role of silicon, include; reduced mineral toxicity, increased photosynthetic activity, superior nutrient imbalance, and enhanced drought and frost tolerance (Ma, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…It also satisfies the requirements, such as, no toxicity to pathogens, plants or animals, not affecting plant growth, development and yield, broad spectrum of defense and long lasting (Kessman et al, 1994;Tally et al, 1999;Kuc, 2001). There were several studies in the past proved that the enhanced natural disease resistance could be achieved with silicon (Si) treatment, in a wide range of tropical and sub-tropical fruits and vegetables (Weerahewa and Somapala, 2016;Huang et al, 2011;French-Monar et al, 2010). This has been achieved through different role of silicon, include; reduced mineral toxicity, increased photosynthetic activity, superior nutrient imbalance, and enhanced drought and frost tolerance (Ma, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Most of the studies showed that seed treatment with synthetic fungicides and foliar application of synthetic fungicide are most effective to control rice grain discoloration disease (Agarwal et al, 1989;Arshad et al, 2009). However, continuous use of fungicides can lead to health and environmental problems (Korndorfer et al, 1999) and development of fungicide resistance of pathogen populations (Jayawardana and Weerahewa, 2016). Therefore, to address the current demand in sustainable crop production and concern of food safety, environmental friendly alternatives should be investigated to control rice grain discoloration disease.…”
Section: Introductionmentioning
confidence: 99%
“…Si is beneficial for plants in terms of yield (Ghasemi et al, 2013), growth and resistance to biotic and abiotic stresses (Datnoff et al, 1992). Addition of Si can decrease the incidence of several diseases in rice such as blast, brown spot, sheath blight, grain discoloration and disease bacterial leaf blight (Jayawardana and Weerahewa, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations